2021
DOI: 10.1096/fj.202001098r
|View full text |Cite
|
Sign up to set email alerts
|

St. John’s Wort alleviates dextran sodium sulfate‐induced colitis through pregnane X receptor‐dependent NFκB antagonism

Abstract: St. John's wort (SJW), from traditional herbs, activates the pregnane X receptor (PXR), a potential drug target for treating inflammatory bowel disease (IBD).However, how SJW alleviates dextran sodium sulfate (DSS)-induced experimental IBD by activating PXR is unknown. To test this, PXR-humanized, wild-type (WT) and Pxr-null mice, primary intestinal organoids cultures, and the luciferase reporter gene assays were employed. In vivo, a diet supplemented with SJW was found to activate intestinal PXR both in WT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…We and other authors have previously reported that HPF and SJW extract had the ability to hinder NF-κB activation [ 33 , 34 , 56 , 69 , 70 ]. Many data demonstrate that NF-κB can be a specific target for counteracting melanoma progression [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…We and other authors have previously reported that HPF and SJW extract had the ability to hinder NF-κB activation [ 33 , 34 , 56 , 69 , 70 ]. Many data demonstrate that NF-κB can be a specific target for counteracting melanoma progression [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although substantial PXR-activating xenobiotics have been reported to exert immunosuppressive effects ( Wallace et al, 2010 ; Kittayaruksakul et al, 2013 ; Zhang J. et al, 2015 ; Rosette et al, 2019 ), the human PXR agonist rifampin is not an ideal choice for anti-inflammation treatment due to its adverse effects. The herbal PXR activators such as St. John’s Wort and Schisandra sphenanthera (Wuweizi) have been used for a long time which may serve as a beneficial alternative medicine for inflammatory diseases ( Mu et al, 2006 ; Yan et al, 2021 ). TanIIA is a bioactive compound derived from the root of Salvia miltiorrhiza and has been demonstrated as a PXR activator in various diseases ( Yu et al, 2009 ; Zhang et al, 2015a ; Zhang et al, 2015b ; Zhu et al, 2017 ; Liu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic diseases are often accompanied by systemic inflammations. It is also widely recognized that chronic inflammation plays a critical role in the initiation and progression of metabolic diseases (Baker et al, 2011) St. John's wort, a PXR agonist, can activate PXR and further inhibit tumor necrosis factor (TNF) α-induced NF-κB translocation and activation (Yan T. et al, 2021). Intestinal PXR activation exerts a protective effect in the context of inflammatory bowel disease (IBD), and this is partially due to the attenuation of NF-κB signaling that leads to lower expression of cytokines (Cheng J. et al, 2012).…”
Section: Roles Of Pxr In Innate Immunitymentioning
confidence: 99%